Pengaruh Green Perceived Value Terhadap Consumer Attitude Dalam Pengurangan Penggunaan Kantong Plastik Di Kota Palembang Dengan Pro Environtmental Behavior Sebagai Mediator - winda Fuji Lestari; Okta Dian Sari (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2026)
This research investigates how the green perceived value of environmentally friendly practices impacts consumer attitudes towards reducing plastic bag usage, with pro environtmental behaviors serving as a mediating element. A quantitative research method was utilized, gathering data from 120 consumers in modern retail settings within Palembang City through a carefully designed questionnaire. The data analysis was carried out using Partial Least Square Structural Equation Modeling, specifically with SmartPLS 3. 0. The findings indicate that the green perceived value related to green practices has a significant and positive effect on both pro environmental behaviors and consumer attitudes. Furthermore, pro environmental behaviors also significantly and positively influence consumer attitudes. Mediation analysis shows that these pro environtmental behaviors partially mediate the connection between the green perceived value and consumer attitudes. These results emphasize the vital role of green perceived value in enhancing environmental sensitivity, which in turn cultivates positive consumer attitudes towards sustainable behaviors. This research adds to the body of knowledge on consumer behavior and sustainability by highlighting how psychological elements are crucial in advancing environmental initiatives. From a practical standpoint, the results suggest that both policymakers and retailers should work on boosting consumers' green perceived value and environmental awareness to make plastic reduction programs more effective.